Valued life abilities among veteran cancer survivors. (29th January 2015) - Karel, Michele J.; Mulligan, Elizabeth A.; Walder, Annette; Martin, Lindsey A.; Moye, Jennifer; Naik, Aanand D.
Abstract: Background: When patients have multiple chronic illnesses, it is not feasible to provide disease‐based care when treatments for one condition adversely affect another. Instead, health‐care delivery requires a broader person‐centred treatment plan based on collaborative, patient‐oriented values and goals. Objective: We examined the individual variability, thematic content, and sociodemographic correlates of valued life abilities and activities among multimorbid veterans diagnosed with life‐altering cancer. Setting and participants: Participants were 144 veterans in the 'Vet‐Cares' study who completed a health‐care values and goals scale 12 months after diagnosis of head and neck, gastro‐oesophageal, or colorectal cancer. They had mean age of 65 years and one quarter identified as Hispanic and/or African American. Design: At twelve months post‐diagnosis, participants rated 16 life abilities/activities in their importance to quality of life on a 10‐point Likert scale, during an in‐person interview. Scale themes were validated via exploratory factor analysis and examining associations with sociodemographic variables. Results: Participants rated most life abilities/activities as extremely important. Variability in responses was sufficient to identify three underlying values themes in exploratory factor analysis: self‐sufficiency, enjoyment/comfort, and connection to family, friends and spirituality. Veterans with a spouse/partner rated self‐sufficiency as less important. African American veterans rated connection as more important than did White veterans. Conclusions: It is feasible yet challenging to ask older, multimorbid patients to rate relative importance of values associated with life abilities/activities. Themes related to self‐sufficiency, enjoyment/comfort in daily life and connection are salient and logically consistent with sociodemographic traits. Future studies should explore their role in goal‐directed health care.